THE EFFECT OF USING KWL(KNOW-WANT-LEARNED) STRATEGY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 12 PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Kiki Yuliana; Effendy Gultom; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This is a pre-experimental research. The aim is to find out whether there is a significant effect of KWL (Know-Want-Learned) strategy on the ability of the first year students of SMAN 12 Pekanbaru in comprehending narrative texts. The design of the study is one group pretest-treatment-posttest design. Cluster sampling technique is used to select one class to become the sample. 35 first year students were chosen as the sample. The results of the data analysis shows that the mean score of the pre-test is66.93 and the mean score of the post-test is 77.36. In other words, the mean score of the post-test was higher than the pre-test. The result also shows that the value of t-test is higher than the t-table (18.43>2.03) at the significance level of 5%. Therefore, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. It can be concluded that there is an effect of using KWL (Know-Want-Learned) strategy on the ability of the first year students of SMAN 12 Pekanbaru in comprehending narrative texts.Keywords: Effect, KWL, Ability, Reading Comprehension, Narrative Texts.